Oriented Magnetite Inclusions in Plagioclase: Implications for the Anisotropy of Magnetic Remanence. (24th February 2022) - Ageeva, O.; Habler, G.; Gilder, S. A.; Schuster, R.; Pertsev, A.; Pilipenko, O.; Bian, G.; Abart, R.
Abstract: Micron to sub‐micron sized ferromagnetic inclusions in rock forming silicate minerals may give rise to particularly stable remanent magnetizations. When a population of inclusions have a preferred crystallographic or shape orientation in a rock, the recorded paleomagnetic direction and intensity may be biased by magnetic anisotropy. To better understand this effect, we investigated plagioclase grains from oceanic gabbro dredged from the Mid‐Atlantic Ridge at 11°–17°N. The plagioclase grains contain abundant needle and lath shaped magnetite inclusions aligned along specific directions of the plagioclase lattice. Electron back scatter diffraction and anisotropy of magnetic remanence measurements are used to correlate the orientation distribution of the magnetite inclusions in the host plagioclase that contains multiple twin types (Manebach, Carlsbad, Albite, and Pericline) with the bulk magnetic anisotropy of the inclusion‐host assembly. In non‐modified plagioclase, the anisotropy ellipsoid of magnetic remanence has oblate shapes that parallels the plagioclase (010) plane. It is suggested that recrystallization of magnetite inclusions during hydrothermal overprint shifts the relative abundance of the inclusions pertaining to the different orientation classes. We show that the maximum axis of the anisotropy ellipsoid of magnetic remanence parallels the plagioclase [001] direction, which in turn controls the recorded remanent magnetization direction. Our results are relevant for paleointensity and paleodirection determinations and for the interpretation of magnetic fabrics. Plain Language Summary: Understanding how the Earth's magnetic field has varied in the past depends on the recording fidelity of the remanent magnetization held within the magnetic minerals in rocks, with magnetite being the most common. Magnetite may occur as tiny inclusions in host minerals such as plagioclase, and when they do, they are particularly robust magnetic recorders. Plagioclase from mafic plutonic rocks often contains needle‐shaped magnetite inclusions whose orientations are fixed along specific crystallographic directions of the plagioclase, which leads to extreme magnetic anisotropy. The anisotropy can significantly bias magnetic recording by deflecting the magnetization direction into the magnetic foliation plane or the lineation direction, which may be at high angles from the magnetic field direction. By combining optical and electron microscopy with magnetic measurements of individual magnetite bearing plagioclase grains, we show that different types of crystallographic twinning in plagioclase dictates different crystallographic orientation directions of the magnetite inclusions; the resultant anisotropic distribution of magnetite crystals in turn controls the direction of the magnetic remanence. Key Points: Plagioclase from oceanic gabbro contains needle shaped magnetite inclusions that render plagioclase grains ferromagnetic Most of the needle elongation directions lie within or near the plagioclase (010) plane leading to pronounced magnetic anisotropy The remanent magnetization direction of the magnetite‐bearing plagioclase is controlled by magnetic anisotropy